Overview of the Cardiotoxicity Induced by PD-1/PD-L1 Immune Checkpoint Inhibitor in Critical Care - Ruiting Li; Xiaojing Zou; Huaqing Shu; You Shang (Intensive Care Research, 2021)
Abstract The Programmed Cell Death 1 (PD-1)/Programmed Death Ligand 1 (PD-L1) Immune Checkpoint Inhibitors (ICIs), have become a hot spot in the feld of cancer research and treatment, and bring new hope to patients with advanced tumors. But, in addition to enhancing the anti-tumor effect of T cells, PD-1/PD-L1 inhibitors can also abnormally enhance the immune response, leading to the imbalance of immune tolerance. So, the adverse reactions of multiple system damage, including cardiotoxicity, which are named as immune-related adverse events, emerged one after another. PD-1/PD-L1 inhibitors-related cardiotoxicity is rare but fatal T-cell-driven drug reaction, which includes myocarditis, pericardial disease, vasculitis, Takotsubo syndrome, etc. The incidence of cardiotoxicity is not over 1%, but with high mortality. In recent years, with the popularity of PD-1/PD-L1 ICIs, increasing patients have been admitted to critical care because of severe or fatal cardiotoxicity. At present, adverse cardiac events caused by cardiotoxicity is not systematically reviewed, Intensive care physicians know little about this, and its treatment experience is even less. This review focuses on current knowledge about severe adverse cardiac events caused by PD-1/PD-L1 inhibitors. This study aimed to improve the intensive care physician’s understanding and attention to cardiotoxicity induced by PD-1/PD-L1 inhibitors.